What helps or hinders the transformation from a major tertiary center to a major trauma center? Identifying barriers and enablers using the Theoretical Domains Framework. Issue 1 (December 2016) - Roberts, Neil; Lorencatto, Fabiana; Manson, Joanna; Brundage, Susan; Jansen, Jan
Abstract Background Major Trauma Centers (MTCs), as part of a trauma system, improve survival and functional outcomes from injury. Developing such centers from current teaching hospitals is likely to generate diverse beliefs amongst staff. These may act as barriers or enablers. Prior identification of these may make the service development process more efficient. The importance of applying theory to systematically identify barriers and enablers to changing clinical practice in emergency medicine has been emphasized. This study systematically explored theory-based barriers and enablers towards implementing the transformation of a tertiary hospital into a MTC. Our goal was to demonstrate the use of a replicable method to identify targets that could be addressed to achieve a successful transformation from an organization evolved to provide a particular type of clinical care into a clinical system with different demands, requirements and expectations. Methods The Theoretical Domains Framework (TDF) is a tool designed to elicit and analyze beliefs affecting behavior. Semi-structured interviews based around the TDF were conducted in a major tertiary hospital in Scotland due to become a MTC with a purposive sample of major stakeholders including clinicians and nurses from specialties involved in trauma care, clinical managers and administration. Belief statements were identified through qualitative analysis, and assessed for importance according to prevalence, discordance and evidence base. Results and discussion 1728 utterances were recorded and coded into 91 belief statements. 58 were classified as important barriers/enablers. There were major concerns about resource demands, with optimism conditional on these being met. Distracting priorities abound within the Emergency Department. Better communication is needed. Staff motivation is high and they should be engaged in skills development and developing performance improvement processes. Conclusions This study presents a systematic and replicable method of identifying theory-based barriers and enablers towards complex service development. It identifies multiple barriers/enablers that may serve as a basis for developing an implementation intervention to enhance the development of MTCs. This method can be used to address similar challenges in developing specialist centers or implementing clinical practice change in emergency care across both developing and developed countries.